Improving multiple sclerosis management and collecting safety information in the real world: the MSDS3D software approach. Issue 4 (3rd April 2018) - Haase, Rocco; Wunderlich, Maria; Dillenseger, Anja; Kern, Raimar; Akgün, Katja; Ziemssen, Tjalf
ABSTRACT: Introduction : For safety evaluation, randomized controlled trials (RCTs) are not fully able to identify rare adverse events. The richest source of safety data lies in the post-marketing phase. Real-world evidence (RWE) and observational studies are becoming increasingly popular because they reflect usefulness of drugs in real life and have the ability to discover uncommon or rare adverse drug reactions. Areas covered : Adding the documentation of psychological symptoms and other medical disciplines, the necessity for a complex documentation becomes apparent. The collection of high-quality data sets in clinical practice requires the use of special documentation software as the quality of data in RWE studies can be an issue in contrast to the data obtained from RCTs. The MSDS3D software combines documentation of patient data with patient management of patients with multiple sclerosis. Following a continuous development over several treatment-specific modules, we improved and expanded the realization of safety management in MSDS3D with regard to the characteristics of different treatments and populations. Expert opinion : eHealth-enhanced post-authorisation safety study may complete the fundamental quest of RWE for individually improved treatment decisions and balanced therapeutic risk assessment. MSDS3D is carefully designed to contribute to every single objective in this process.